State of the environment as a determinant of life quality: a local scale approach - Gunko, Ruslan (fi=Turun yliopisto|en=University of Turku|, 2022)
Traditionally nature plays a significant role for people worldwide. Thousands of years ago our ancestors made their life-related decisions by accounting for the environmental situation. They relied on natural phenomena, divinized and defied them. Due to the high dependence on the resources provided by the surrounding environment, people were vulnerable, and changes in environmental conditions motivated them towards migration processes and search for ways of communication. In the 21st century this link to the local environment is not so clear for many people and the role of nature for well-being appears to be disappearing in the shadow of traditional socio-economic factors affecting life quality. However, in circumstances of the global environmental crisis caused by climate change, local nature becomes an important indicator of stress with impact on society. At the same time, the role of local nature for well-being of community is not well known. In this thesis, I studied the impact of the local environment on people’s well-being reflected by the sea surface water quality for inhabitants of a coastal community. These environmental conditions were measured objectively with professional scientific equipment and subjectively by surveying people, who made general assessments of their local environmental conditions. First, I investigated if and how accurately respondents’ perception of water quality corresponds with objective measures, and if socio-demographic status can affect people’s evaluations. My findings suggest that the accuracy of assessing water quality is high and potentially adequate for considering their use in policymaking. Over 70% of people assessed the state of water quality in the right direction and almost 60% were correct in their estimates. At the same time, socio-demographic status had an effect on perceptions but did not markedly improve their reliability. Next, I tested the effect of the local environmental conditions (objectively measured and perceived) on the well-being of individuals in combination with traditional socio-economic factors. I found that the objectively measured state of the environment has a less pronounced impact on life quality, but that the way people perceive their surrounding environmental (water) quality plays a significant role for well-being (life quality). This finding highlights the psychological effect of how the local environment is perceived. Moreover, the strength of this positive relationship between life quality and water quality is conditional on income level, such that people with income issues are more dissatisfied with their life regardless of the quality of surrounding environmental. In my third chapter, I found that local nature can buffer the adverse impacts of global stress on the life quality of individuals. My investigation of the changes in life quality before and during the COVID-19 pandemic indicated that there is a significant role of good environmental conditions for mitigation of the personal impacts of the pandemic. I found that the pandemic had a negative impact on well-being, especially for people who lived in areas with poor coastal water quality. Additionally, I found that the pandemic changed the people-nature relationship toward environmentally-friendly behavior. Lastly, I studied if property prices are influenced by local environmental conditions and whether environmental aspects generate economic benefits through a positive effect on property prices, presented by price perception extracted from real estate listings. My findings indicate that people responsible for the price perception value, property owners and real estate agents, do take into consideration the water quality conditions in their evaluation, and that good water quality corresponds with higher property prices in advertisements. The results of this thesis highlight the significant role of the local environment for life quality of community members. Based on the results, I conclude that local environmental conditions can be buffer to stress impacts, which is important in light of the negative effects of the climate change crisis that small communities are exposed to. This thesis suggests that local councils should involve residents in decision-making and thereby promote environmental democracy.